2005
DOI: 10.1016/j.clpt.2005.01.009
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of goldenseal, kava kava, black cohosh, and valerian on human cytochrome P450 1A2, 2D6, 2E1, and 3A4/5 phenotypes

Abstract: Objectives-Phytochemical-mediated modulation of cytochrome P-450 activity may underlie many herb-drug interactions. Single time-point, phenotypic metabolic ratios were used to determine whether long-term supplementation of goldenseal (Hydrastis canadensis), black cohosh (Cimicifuga racemosa), kava kava (Piper methysticum), or valerian (Valeriana officinalis) extracts affected CYP1A2, CYP2D6, CYP2E1, or CYP3A4/5 activity.Methods-Twelve healthy volunteers (6 females) were randomly assigned to receive goldenseal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
4
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(207 citation statements)
references
References 57 publications
(100 reference statements)
8
189
4
6
Order By: Relevance
“…As examples, some recent clinical studies (Piscitelli et al, 2002a,b;Gurley et al, 2004Gurley et al, , 2005 found that specific preparations of some NHPs used in this study (e.g., milk thistle and goldenseal), known to contain constituents that are P-gp substrates and capable of inhibiting CYP3A4 (and/or other CYP isoforms) metabolism in vitro, had little impact on the overall metabolism of many concomitantly administered drugs (including some HIV protease inhibitors). Although the extrapolation of the current in vitro findings and those from the concurrent study to clinical effects may well be considered speculative, the overall in vitro data should still be considered as a signal of potential in vivo interactions.…”
Section: Discussionmentioning
confidence: 99%
“…As examples, some recent clinical studies (Piscitelli et al, 2002a,b;Gurley et al, 2004Gurley et al, , 2005 found that specific preparations of some NHPs used in this study (e.g., milk thistle and goldenseal), known to contain constituents that are P-gp substrates and capable of inhibiting CYP3A4 (and/or other CYP isoforms) metabolism in vitro, had little impact on the overall metabolism of many concomitantly administered drugs (including some HIV protease inhibitors). Although the extrapolation of the current in vitro findings and those from the concurrent study to clinical effects may well be considered speculative, the overall in vitro data should still be considered as a signal of potential in vivo interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Grapefruit juice is a particularly well-known inhibiting agent towards numerous CYP enzymes, both in vitro and in vivo, with clinically relevant changes in metabolism of conventional medicines (Hanley et al 2011). Kava and Ginkgo biloba have also shown effects in vivo, with significant changes in drug metabolism and clinical effects in humans (Gurley et al 2002(Gurley et al , 2005Abad et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…However, critical assessment of these studies suggests that the clinical relevance of the findings is questionable due to various methodological limitations (Table 1). This is underlined by the available clinical interaction studies on CYP isoenzymes, which do not indicate a relevant drug interaction potential of valerian in healthy volunteers [35,37].…”
Section: Discussionmentioning
confidence: 99%
“…One of these publications [34] contains, in addition, data on animal studies. Two publications [35,37] present clinical studies on pharmacokinetic interactions. 8 studies are available on the subject of pharmacodynamic interactions, thereof two in vitro and three animal studies, one clinical study, and in addition two case reports.…”
Section: Metabolic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation